Causal Attribution Profiles as a Function of Reading Skills, Hyperactivity, and Inattention. (4th May 2019) - Tsujimoto, Kimberley C.; Boada, Richard; Gottwald, Stephanie; Hill, Dina; Jacobson, Lisa A.; Lovett, Maureen; Mahone, E. Mark; Willcutt, Erik; Wolf, Maryanne; Bosson-Heenan, Joan; Gruen, Jeffrey R.; Frijters, Jan C.
ABSTRACT: The causes that individuals attribute to reading outcomes shape future behaviors, including engagement or persistence with learning tasks. Although previous reading motivation research has examined differences between typical and struggling readers, there may be unique dynamics related to varying levels of reading and attention skills. Using latent profile analysis, we found 4 groups informed by internal attributions to ability and effort. Reading skills, inattention, and hyperactivity/impulsivity were investigated as functional correlates of attribution profiles. Participants were 1, 312 youth (8–15 years of age) of predominantly African American and Hispanic racial/ethnic heritage. More adaptive attribution profiles had greater reading performance and lower inattention. The reverse was found for the least adaptive profile with associations to greater reading and attention difficulties. Distinct attribution profiles also existed across similar-achieving groups. Understanding reading-related attributions may inform instructional efforts in reading. Promoting adaptive attributions may foster engagement with texts despite learning difficulties and, in turn, support reading achievement.